Challenges in Schooling of Muslim Minority Children : A Review of Policies and Programmes in India - Sedwal, Mona (JOURNAL OF INDIAN EDUCATION, 2024)
The Constitution of India has established various provisions to safeguard the interests of minority groups. At national level, Muslims constitute the largest minority, comprising approximately 17.22 crores or 14.2 per cent of India’s total population. India is home to nearly 11 per cent of the global Muslim population, ranking third in terms of Muslim population after Indonesia and Pakistan. According to the 2011 Census, Muslims have the highest percentage of illiteracy at 42.7 per cent. To address the concerns of minority communities, including Muslims, the Ministry of Minority Affairs was established as an apex body. The Ministry is tasked with formulating overall policies and plans to address issues affecting notified minority groups. The Sachar Committee Report of 2006 extensively reviewed the educational status of minority communities highlighting their educational backwardness, economic marginalisation, and social exclusion. This paper reviews progress in participation of Muslim minority children in schools by reviewing policies and programmes related to access and participation post-2006. It also explores the issues and challenges on the educational development and socio-economic upliftment of the Muslim community with particular reference to Madarsas. It further investigates the prospects for addressing these issues within the framework of the National Education Policy (NEP) 2020